Development of a human-robot interaction system - Man, Pui Suen (2018)
In the past few decades, industrial robots have been increasingly and rapidly populating many industries. With today’s advancements in technology, it is almost certain that robotics will be gradually taking over various industries, especially the manufacturing industry. This paper will be discussing about the safety issues regarding a Human Robot Interaction (HRI) in the same working space after briefly introducing about the industrial robots. The project conducted will be introducing a new anti-collision function that can be easily implemented to any consumers’ and companies’ pre-owned industrial robots. Usually, the introduction of such new functions requires the repurchase of a brand new robot which is extremely costly. However, this paper will be proposing a function that requires only add-on components that can be easily attached to any robots. With the addition of such components, the robot will be able to detect and respond simultaneously in the event of contact by any humans or objects. This paper elaborated on how this new function is applied to a commonly used industrial robot, the SCARA robot. The results will be presented.